Magnetron Sputter Epitaxy of High-Quality GaN Nanorods on Functional and Cost-Effective Templates/Substrates - Elena Alexandra Serban; Justinas Palisaitis; Muhammad Junaid; Lina Tengdelius; Hans Högberg; Lars Hultman; Per Ola Åke Persson; Jens Birch; Ching-Lien Hsiao (Energies, 2017)
We demonstrate the versatility of magnetron sputter epitaxy by achieving high-quality GaN nanorods on different substrate/template combinations, specifically Si, SiC, TiN/Si, ZrB2/Si, ZrB2/SiC, Mo, and Ti. Growth temperature was optimized on Si, TiN/Si, and ZrB2/Si, resulting in increased nanorod aspect ratio with temperature. All nanorods exhibit high purity and quality, proved by the strong bandedge emission recorded with cathodoluminescence spectroscopy at room temperature as well as transmission electron microscopy. These substrates/templates are affordable compared to many conventional substrates, and the direct deposition onto them eliminates cumbersome post-processing steps in device fabrication. Thus, magnetron sputter epitaxy offers an attractive alternative for simple and affordable fabrication in optoelectronic device technology.